Effect of feedback on cycling performance in a 4-kilometres laboratory time trial - Lugo, H.; Chakravorti, N.; Philpott, L.; Crewther, B.; Conway, P.; West, A. (Journal of Science and Cycling, 2015)
Background: Nowadays performance data (e.g. power, speed, cadence) are available to cyclists in real time. The availability and manipulation of the data can be used to change activity parameters (e.g. pedaling dynamics) (Bibbo et al., 2012: Image Processing: Algorithms and Systems X; and Parallel Processing Imaging Applications II, Conference Volume 8295) or be used to, by introducing a deception component, access metabolic reserves (Stone et al., 2011: Medicine & Science in Sports & Exercise, 44(3), 534 541). To date the effect of feedback has mainly been analysed based on a deception component. However, the effect of removing the feedback altogether on performance has not been reported.